KEBUTUHAN IBU YANG MENGALAMI HIV/AIDS DALAM MERAWAT ANAK DENGAN HIV DI RUMAH CEMARA KOTA BANDUNG : STUDI KUALITATIF - Eli Lusiani (Jurnal Asuhan Ibu dan Anak, 2018)
The case of Human Immunodeficiency Virus (HIV) has increased every year. HIV disease causes death in mothers and children. The needs of mothers who have HIV in producing children are diverse, including biological needs, psychological needs for laboratory examination, or special education for HIV-infected children. This study aims to explore in depth the needs of HIV-infected mothers in caring for HIV-infected children in pine house Bandung. This research is a qualitative research with descriptive explorative design. Participants in this study were mothers who had HIV who had an HIV child with a total of 8 people. Data collection by in-depth interview of Discusion Group Focus (FDG). Data analysis using thematic analysis according to Collaizz's method. The results of the study are eight themes: 1) knowledge of mothers who have HIV in caring for children of HIV, 2) challenges of mothers who have HIV in caring for children of HIV, 3) biological needs of mothers who have HIV in caring for children of HIV, 4) psychological needs of mothers who experience HIV in caring for children of HIV, 5) Educational needs for children with HIV, 6) Need for Labolatory check up, 7) Support / Social Support, 8) Positive expectation of HIV-infected mother in caring for HIV-infected children. Based on the results of the study it is recommended that nurses can act as educators and informants for families of patient with HIV / AIDS, become advocates, and also become a motivator. For further investigators can examine the basic human needs of adolescents with HIV / AIDS. The case of Human Immunodeficiency Virus (HIV) has increased every year. HIV disease causes death in mothers and children. The needs of mothers who have HIV in producing children are diverse, including biological needs, psychological needs for laboratory examination, or special education for HIV-infected children. This study aims to explore in depth the needs of HIV-infected mothers in caring for HIV-infected children in pine house Bandung. This research is a qualitative research with descriptive explorative design. Participants in this study were mothers who had HIV who had an HIV child with a total of 8 people. Data collection by in-depth interview of Discusion Group Focus (FDG). Data analysis using thematic analysis according to Collaizz's method. The results of the study are eight themes: 1) knowledge of mothers who have HIV in caring for children of HIV, 2) challenges of mothers who have HIV in caring for children of HIV, 3) biological needs of mothers who have HIV in caring for children of HIV, 4) psychological needs of mothers who experience HIV in caring for children of HIV, 5) Educational needs for children with HIV, 6) Need for Labolatory check up, 7) Support / Social Support, 8) Positive expectation of HIV-infected mother in caring for HIV-infected children. Based on the results of the study it is recommended that nurses can act as educators and informants for families of patient with HIV / AIDS, become advocates, and also become a motivator. For further investigators can examine the basic human needs of adolescents with HIV / AIDS.